Strongly lacunary convergence of order 13 of difference sequences of fractional order in neutrosophic normed spaces - Aral, Nazlim Deniz; Kandem, Hacer Senguil; Et, Mikail (Univ Nis, Fac Sci Math, 2023)
In this paper, we introduce the concept of strongly lacunary convergence of order 13 of difference sequences of fractional order in the neutrosophic normed spaces. We investigate a few fundamental properties of this new concept.
Keywords: Statistical convergence; Lacunary sequence; Fractional difference operator; Metric space